More Ethics Than Politics, More Animals Than Species: Review of Raymond Corbey and Annette Lanjouw, eds. The Politics of Species: Reshaping our Relationships with Other Animals - MacClellan, Joel (Humanimalia, 2016)
Raymond Corbey and Annette Lanjouw, eds. The Politics of Species: Reshaping our Relationships with Other Animals. New York: Cambridge University Press, 2013. 310 pp. $140 (hb).